HEALTH INTERVENTION ON DECREASING ELDERLY DEPRESSION: REVIEW ARTICLE - Afni, Erina Nur; Nugraheni, Sri Achadi (Krafon Publishing, 2019)
Growth of 20-25% prevalence of psychiatric disorders in Iran compared to 21.5% in 2012(1) damage to health, happiness, ability to carry out daily activities(2) and cause 50% of psychosomatic disorders. So that 30% of people referred to the health center suffer from psycho-socio-spiritual problems (1). The inclusion of the spiritual health dimension into the concept of health, introduces an important dimension, for health experts(3).